2024
DOI: 10.3892/etm.2024.12489
|View full text |Cite
|
Sign up to set email alerts
|

Immune profile of patients‑a new approach in management of sepsis and septic shock?

Anca Bacârea,
Oana Coman,
Vladimir Bacârea
et al.

Abstract: The present study was a prospective observational single center study, enrolling 102 patients with sepsis, admitted in the Intensive Care Unit of the County Emergency Clinical Hospital in Târgu Mureș (Mureș, Romania). The main goal of the present study was to compare the changes of the following parameters on day 1 compared with day 5, in sepsis compared with septic shock, as well as in survivors compared with non-survivors: Cell blood count parameters, neutrophil-lymphocyte ratio, platelet-lymphocyte ratio an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 54 publications
0
1
0
Order By: Relevance
“…Mahmoud et al [26] reported high specificity and positive predictive value for the NLR and PLR in detecting early-onset neonatal sepsis (NLR 99% specificity, 98% PPV; PLR 73% specificity, 72% PPV), underscoring their utility as reliable indicators of sepsis in neonates. Similarly, Bacarea et al's [27] analysis in adult sepsis patients highlighted the prognostic significance of dynamic changes in the NLR and PLR, alongside systemic inflammation markers, reinforcing the potential of these biomarkers to reflect the severity and progression of sepsis.…”
Section: Literature Findingsmentioning
confidence: 93%
“…Mahmoud et al [26] reported high specificity and positive predictive value for the NLR and PLR in detecting early-onset neonatal sepsis (NLR 99% specificity, 98% PPV; PLR 73% specificity, 72% PPV), underscoring their utility as reliable indicators of sepsis in neonates. Similarly, Bacarea et al's [27] analysis in adult sepsis patients highlighted the prognostic significance of dynamic changes in the NLR and PLR, alongside systemic inflammation markers, reinforcing the potential of these biomarkers to reflect the severity and progression of sepsis.…”
Section: Literature Findingsmentioning
confidence: 93%